Walkability Microscale Analysis: : Application of MAPS-Global in a low-income neighborhood of a medium-sized Brazilian city. - Desenne Sasaki, Nina (2022)
The walkability microscale includes elements perceived by the pedestrian. To understand the impact of the microscale on walking, audit tools, including MAPS-Global, were developed to measure this relationship. Audits can have two approaches to capturing variables: in locus and online. Studies on the relationship between the built environment and active mobility in low-income neighborhoods in Brazilian cities seem to be limited. The application of MAPS-Global in countries with this profile has gaps to moderate the reliability and validity of virtual audits. The objective of the study is to evaluate the microscale of the built environment and its levels of walkability, through the application of the MAPS-Global tool, in a low-income neighborhood of a medium-sized Brazilian city. The empirical study was conducted in Londrina/PR in the Cinco Conjuntos neighborhood. A pilot study was conducted to verify the reliability between auditors and then apply the tool to the entire neighborhood using Google Street View images. The collected data were tabulated in scores, according to the MAPS-Global Data Dictionary. The scores obtained, in general, were low, which indicates that the neighborhood has unfavorable microscale characteristics for walking.